The Postoperative Pain Assessment Skills Pilot Trial - Michael McGillion; Adam Dubrowski; Robyn Stremler; Judy Watt-Watson; Fiona Campbell; Colin McCartney; J Charles Victor; Jeffrey Wiseman; Linda Snell; Judy Costello; Anja Robb; Sioban Nelson; et al. (Pain Research and Management)
BACKGROUND/OBJECTIVES: Pain-related misbeliefs among health care professionals (HCPs) are common and contribute to ineffective postoperative pain assessment. While standardized patients (SPs) have been effectively used to improve HCPs’ assessment skills, not all centres have SP programs. The present equivalence randomized controlled pilot trial examined the efficacy of an alternative simulation method – deteriorating patient-based simulation (DPS) – versus SPs for improving HCPs’ pain knowledge and assessment skills.